2020
DOI: 10.1242/dev.184341
|View full text |Cite
|
Sign up to set email alerts
|

The RNA helicase DDX3 induces neural crest by promoting AKT activity

Abstract: Mutations in the RNA helicase DDX3 have emerged as a frequent cause of intellectual disability in humans. Because many individuals carrying DDX3 mutations have additional defects in craniofacial structures and other tissues containing neural crest (NC)-derived cells, we hypothesized that DDX3 is also important for NC development. Using Xenopus tropicalis as a model, we show that DDX3 is required for normal NC induction and craniofacial morphogenesis by regulating AKT kinase activity. Depletion of DDX3 decrease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 88 publications
2
12
0
Order By: Relevance
“…Rather than directly modulating elements of the Wnt/β-catenin pathway, the authors found that DDX3 regulates the serine/threonine kinase, AKT, in an RNA helicase-dependent manner. In the NC, DDX3 RNA helicase activity stimulates AKT, which phosphorylates and inhibits Gsk3β, resulting in the accumulation of β-catenin ( Perfetto et al, 2021 ). AKT is also regulated upstream by phosphatidylinositol 3-kinase (PI3K) implicated in NC induction ( Ciarlo et al, 2017 ).…”
Section: Further Levels Of Wnt/β-catenin Signalling and Nc Inductionmentioning
confidence: 99%
“…Rather than directly modulating elements of the Wnt/β-catenin pathway, the authors found that DDX3 regulates the serine/threonine kinase, AKT, in an RNA helicase-dependent manner. In the NC, DDX3 RNA helicase activity stimulates AKT, which phosphorylates and inhibits Gsk3β, resulting in the accumulation of β-catenin ( Perfetto et al, 2021 ). AKT is also regulated upstream by phosphatidylinositol 3-kinase (PI3K) implicated in NC induction ( Ciarlo et al, 2017 ).…”
Section: Further Levels Of Wnt/β-catenin Signalling and Nc Inductionmentioning
confidence: 99%
“…Notably, however, knockdown or ablation of Esrp1/2 , Rbfox2 , Srsf3 and Ddx3x each results in altered expression of transcripts encoding components of developmental signaling pathways. These include the FGF, WNT, SHH, BMP and TGFβ signaling pathways in the case of ESRP1/2 [ 30 ], and the TGFβ, PDGF and Wnt signaling pathways for RBFOX2 [ 48 ], SRSF3 [ 58 ] and Ddx3x [ 70 , 72 ], respectively. These findings raise the intriguing possibility that RNA processing mediated by RBPs serves to regulate both intracellular and intercellular signaling during craniofacial development, often in feedback loops involving developmental signaling pathways and the phosphorylation of intracellular effectors.…”
Section: Discussionmentioning
confidence: 99%
“…These defects stem from reduced expression of transcripts encoding proteins involved in neural plate border specification, including pax3 and msx1 , and NC specification, including snai2 and sox9 , at the end of gastrulation. Moreover, the function of Ddx3 in this context is mediated by the downstream effector Rac1, leading to activation of Akt, the subsequent phosphorylation and inhibition of Gsk3β, and ultimately the stabilization of two proteins required for NC induction, β-catenin and Snai1 [ 70 ].…”
Section: Rbps Involved In Translationmentioning
confidence: 99%
“…It was suggested that DHX29 carries additional roles beyond translation, such as recognizing double-stranded RNA and specific interaction with melanoma differentiation-associated protein 5 (MDA5) to enhance innate antiviral immunity [45]. Interestingly, other DEAD/H box RNA helicases have also been shown to affect Wnt signaling; DDX3 was shown to be a regulatory subunit of CK1 that regulates canonical Wnt signaling [46,47], and DDX3 knockdown was recently shown to inhibit AKT activity and Wnt signaling [48]. DHX15 has been shown to mediate Wntinduced antimicrobial protein expression in specific colonic cells [49].…”
Section: Discussionmentioning
confidence: 99%